Institutional investors and equity returns: Are short-term institutions better informed? - YAN, Xuemin (Sterling) (Institutional Knowledge at Singapore Management University, 2009)
We show that the positive relation between institutional ownership and future stock returns documented in Gompers and Metrick (2001) is driven by short-term institutions. Furthermore, short-term institutions' trading forecasts future stock returns. This predictability does not reverse in the long run and is stronger for small and growth stocks. Short-term institutions' trading is also positively related to future earnings surprises. By contrast, long-term institutions' trading does not forecast future returns, nor is it related to future earnings news. Our results are consistent with the view that short-term institutions are better informed and they trade actively to exploit their informational advantage.